Metrics for Quantification of By-Process Segregation in Ge-Rich GST - Petroni, Elisa; Serafini, Andrea; Codegoni, Davide; Targa, Paolo; Mariani, Luca; Scuderi, Mario; Nicotra, Giuseppe; Redaelli, Andrea (Frontiers in Physics, 2022)
Ge-rich GST alloys are the most promising materials for phase-change memory (PCM) to fulfill the soldering compliance and the tough data retention requirements of automotive applications. Significant efforts have been made to engineer those materials and optimize their integration inside the fabrication process of PCM. In this perspective, the physical characterization of the device and the material is instrumental in understanding the underlying physics, improving the process, and optimizing the interactions between the device, the process, and the material itself. Especially, microscopic investigations have gathered increasing interest, giving detailed descriptions of local material modulations that have a crucial role in cell programming and reliability performances. In this work, a deep analysis of Ge-rich GST microscopic alloy evolution during the integration process has been performed, exploiting analysis by EELS with TEM supported by a novel statistical data post-processing method. The new proposed statistical-based methodology also introduces new simple metrics for elemental compositional evaluations that have been exploited for process engineering.